A study of awarding student achievement using blockchain - Ansari, Mohammed Rehan; Navratan, Navratan; Umamaheswari, K. M. (Linguistics and Culture Review, 2021)
Blockchain technology will soon have progressed from being an innovation to the norm of application development and the digital revolution. The technology of a blockchain is essential based on a widely distributed, peer-to-peer ledger of transactions and balances. This ledger is essentially a huge database broken down into chunks known as blocks. These blocks and the entire ledger are stored in millions of copies on that particular blockchain network on extremely powerful computers known as nodes. There is a majority-based consensus that exists for every transaction that is carried out and put in a block. To tamper with this ledger would require computing power either equal to or greater than 51% of all the nodes active for that particular blockchain. Even if this power were acquired to tamper with or hack the particular blockchain, the cryptocurrencies or tokens that are transacted on the blockchain would essentially be overturned and considered worthless due to the other nodes detecting a hack or attempt to steal tokens or wallet balances. This is how the first cryptocurrency like bitcoin, along with many other cryptocurrencies on their respective blockchain technologies, operate.